2021
DOI: 10.3390/ruminants1010002
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-Diaphysis Is a Poor Predictor of Humeral Fracture Risk Indicating That Predisposing Factors Are Recent

Abstract: The incidence of spontaneous humeral fractures in first-lactation dairy heifers in New Zealand has emphasised the need to understand the thoracic limb bone growth of dairy heifers. Previous research has indicated that a predisposing factor to spontaneous humeral fracture is nutrition. In addition, it has been hypothesised that liver copper concentration affects bone strength and may be a potential factor associated with humeral fracture risk. The aim of this study was to compare bone morphology in the mid-diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…An increased incidence of spontaneous humeral fractures in primiparous dairy cows in New Zealand has prompted investigations characterizing different parameters that influence bone tissue strength in bone samples from normal and fractured bone material using a variety of techniques ( 1 3 ). For example, histological analysis of bone samples from primiparous cows with humeral fracture determined that cows with humeral fractures developed osteoporosis characterized by decreased bone volume, abnormal trabecular architecture, presence of growth arrest lines, thinner cortex with increased resorption in the cortex and distal humerus ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased incidence of spontaneous humeral fractures in primiparous dairy cows in New Zealand has prompted investigations characterizing different parameters that influence bone tissue strength in bone samples from normal and fractured bone material using a variety of techniques ( 1 3 ). For example, histological analysis of bone samples from primiparous cows with humeral fracture determined that cows with humeral fractures developed osteoporosis characterized by decreased bone volume, abnormal trabecular architecture, presence of growth arrest lines, thinner cortex with increased resorption in the cortex and distal humerus ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were associated with periods of poor bone formation (probably due to protein-calorie undernutrition), increased bone resorption associated with lactation, and periods of copper deficiency ( 1 , 4 ). Peripheral quantitative computed tomography of the mid-diaphysis of the humerus showed that fractured animals had reduced cortical bone mineral density which reduced the stress-strain index ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reported case of spontaneous humeral fracture in primiparous dairy cows in New Zealand, several risk factors have been hypothesized as associated with an increased incidence of fractures [ 1 , 2 , 3 ]. The largest histological study on humeral fractures determined that cows have osteoporosis due to inadequate bone deposition during the first months of the cow’s life and increased bone resorption in the post calving period [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The largest histological study on humeral fractures determined that cows have osteoporosis due to inadequate bone deposition during the first months of the cow’s life and increased bone resorption in the post calving period [ 4 ]. Another study, using peripheral quantitative computed tomography, has shown a consistent trend for reduced bone length and reduced cortical bone mineral density in primiparous cows with humeral fractures compared with age-matched controls [ 3 ]. The findings from both these studies support the hypothesis that periods of inadequate nutrition (most likely protein-calorie undernutrition) act as a contributory factor in the occurrence of humeral fractures in cows and furthermore suggest these changes are recent [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation